1987
DOI: 10.1139/z87-445
|View full text |Cite
|
Sign up to set email alerts
|

Odor preference and social behavior in meadow voles, Microtus pennsylvanicus: seasonal differences

Abstract: FERK~N, M. H., and SEAMON, J. 0 . 1987. Odor preference and social behavior in meadow voles, Microtus pennsylvanicus: seasonal differences. Can. J. Zool. 65: 293 1 -2937. Olfactory cues play a major role in inter-and intra-sexual agonistic behavior for Microtus pennsylvanicus. We show that seasonal changes in odor preference and behavioral interactions coincide with varying patterns of social organization. Odor preference trials were conducted in a Y maze and social behavior was measured in dyadic encounters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 30 publications
6
83
1
Order By: Relevance
“…In addition, it has been suggested by Ylönen et al (1995) that females with their better "social skills" form the core of winter aggregations and that this could play an important role in the overwintering success of the whole overwintering population. Based on the experiment on odor preference, also Ferkin & Seamon (1987) suggested that overwintering groups of meadow voles (Microtus pennsyvanicus) might be female biased, as non-breeding meadow vole females showed preference for the odor of female conspecifics, whereas males showed no preference and displayed more antagonistic acts against other males, than females against female conspecifics. Thus, male-male aggressive interactions may preclude males from joining the same winter aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested by Ylönen et al (1995) that females with their better "social skills" form the core of winter aggregations and that this could play an important role in the overwintering success of the whole overwintering population. Based on the experiment on odor preference, also Ferkin & Seamon (1987) suggested that overwintering groups of meadow voles (Microtus pennsyvanicus) might be female biased, as non-breeding meadow vole females showed preference for the odor of female conspecifics, whereas males showed no preference and displayed more antagonistic acts against other males, than females against female conspecifics. Thus, male-male aggressive interactions may preclude males from joining the same winter aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in day length in laboratory studies trigger at least some of the changes in behavior observed seasonally in the field (Ferkin and Seamon, 1987). In long day lengths (LDs), female meadow voles prefer the odors of males over those of females, consistent with summer breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Idris and Prakash 1986, Ferkin and Seamon 1987, Heske 1987. The influence of odours left in traps on successive trappings of rodents was also analyzed.…”
Section: Discussionmentioning
confidence: 99%